Evaluasi Pemanfaatan Media Pembelajaran IPA di SDN Bangkal 2 - Iqroatus Shafiroh; Dewi Sofia Nabilla; Novelia Ariyanti; Yeni Puji Astuti (Jurnal Pengabdian Pendidikan, 2025)
Abstract: This study aims to evaluate the utilization of science learning media at SDN Bangkal 2. Using a descriptive qualitative approach, data were collected through classroom observations and interviews with the third-grade teacher. The findings indicate that three main types of media are used in the learning process, namely environmental objects, visual images, and projectors. These media were found to be effective in improving students’ understanding of scientific concepts. Environmental objects support students’ learning through direct, hands-on experiences, visual images help clarify abstract material, and projectors provide dynamic visualizations that make learning more engaging. Overall, the use of science learning media at SDN Bangkal 2 has been implemented well and contributes positively to the quality of instruction.